Parkett : The Parkett series with contemporary artists - ﻿ (Zürich : Parkett-Verlag, 2003)
Table of Content The Starling Variations by Troy Selvaratnam John Bock Ars Combinatoria by Jens Hoffmann Rope Tricks by Daniel Birnbaum Bock-Ness Monster by Jan Avgikos Peter Doig Peter Doig – A Partial Record by Paul Bonaventura Contemporary Fragility by Rudi Fuchs Peter Doig’s Now by Beatrix Ruf Fred Tomaselli Through a Window Darkly by Dan Cameron Transcendence Is Pop by James Rondeau Tomaselli’s Postmodern Gnosticism by Daniel Pinchbeck Marcel Dzama, Insert My Work Ends in Music – Hanne Darboven by Sibylle Omlin The Invention of the Schaulager by Theodora Vischer & Jacques Herzog Wang Fu’s Cycle Prima Materia/Riots, Les Infos du Paradis by Hartmut Böhme Notes on Renewed Appropriation Appropriationisms, Cumulus from America by Lauri Firstenberg Mimetic Moments, Cumulus from Europe by Rita Kersting Underground, Underworld, Understanding, Colin De Land, 1955 – 2003 by Fracesco Bonami Autoreroticism by Daniele Muscionico
﻿John Bock, Peter Doig, and Fred Tomaselli seem to be spelling out a new universe in the act of shaping their personal inventory in space or confining it to a plane. The first paints, the second constructs and gives eccentric lectures, and the third embeds tiny cutouts and real plants under an acrylic veneer. Their points of reference burrow deep into the world and break out of it, oscillating between cosmic and atomistic dimensions. It is as if the universe and its subuniverses were being tidied in order to create startling new complexities, the likes of which, though often conjectured, have never been seen in this form before, for they are certainly not hermetically sealed. On the contrary, they breathe a supra-personal and comprehensible credibility. Are these artists forging, pasting, and even knitting a new concept of authenticity with their matter-of-fact array of curious set pieces? (editorial by publisher)
boek
Keywords: Bock, John; Tomaselli, Fred; Doig, Peter